Naringenin and caffeic acid supplementation alleviates heat stress-induced liver damage by maintaining endoplasmic reticulum homeostasis in broilers - Fredie Robinson; Mohd Firdaus Mohd Hayati; Fong, Siat Yee; J. Chen (Polska Akademia Nauk, 2025)
Heat stress (HS) is a major challenge to poultry production, with significant implications for animal health and performance. This study explored the protective role of naringenin (NAR) and caffeic acid (CA) on liver health in HS-exposed broilers. First, an in vitro screening experiment was performed in chicken embryo fibroblast (DF-1) cells. Our results demonstrated that NAR and CA significantly reduced the expression of heat shock protein 70 (HSP70) and heat shock transcription factor 1 (HSF1), while restoring superoxide dismutase (SOD) activity and total antioxidant capacity (T-AOC) compared to the HS group (P < 0.05). For the in vivo trial, broilers subjected to chronic HS (37 ± 2 °C for 6 weeks) were supplemented with 0.1% NAR, 0.1% CA, or their combination. Dietary NAR and CA significantly improved broiler growth performance under HS. Both compounds markedly reduced serum and liver levels of HSP70 and HSF-1, while enhancing antioxidant capacity (SOD and T-AOC; P < 0.05). Additionally, NAR and CA protected against HS-induced liver damage, as evidenced by reduced serum aspartate transaminase and alanine transaminase activity (P < 0.05). Mechanistically, NAR and CA preserved liver homeostasis by modulating the endoplasmic reticulum stress response signalling involving PKR-like ER kinase, activating transcription factor 4, activating transcription factor 6, eukaryotic translation initiation factor 2 alpha, C/EBP homologous protein, X-box-binding protein 1, and glucose-regulated protein 78.